Synthesis of MIL-100(Fe) at Low Temperature and Atmospheric Pressure - Jing Shi; Shengtao Hei; Huanhuan Liu; Yanghe Fu; Fumin Zhang; Yijun Zhong; Weidong Zhu (Journal of Chemistry)
MIL-100(Fe), a mesoporous metal-organic framework (MOF), has a large BET specific surface area and pore volume with the presence of a significant amount of accessible Lewis acid metal sites upon dehydration. The structural characteristics of MIL-100(Fe) make it a good candidate for potential applications in gas storage, separation, and heterogeneous catalysis. Mainly, this MOF is obtained by the hydrothermal synthesis in a Teflon-lined autoclave at high temperature (>150°C) under static conditions. However, this method has several disadvantages such as high temperature, high (autogenous) pressure, long time, and comparable low MOF yield. Therefore, development of a facile method for synthesis of MIL-100(Fe) is vitally important for fundamental understanding and practical application. Herein, MIL-100(Fe) is synthesized by a facile low-temperature (<100°C) synthesis route at atmospheric pressure by reaction of metallic iron and trimesic acid in water. Due to our synthesis is conducted with agitation, higher MOF yield (>90%) still could be achieved, suggesting that this simple and energy saving method has the potential to be used practically.